Thomas Elyot, critical editions of four works on counsel : The doctrinal of princes, Pasquill the playne, Of that knowlage whiche maketh a wise man, and The defence of good women - Elyot, Thomas, Sir, 1490?-1546. (International Studies in the History of Rhetoric, 2018)
This volume provides the first modern scholarly editions of four works on the rhetoric of counsel by Sir Thomas Elyot (1490-1546), humanist scholar and advisor to Henry VIII of England. The Doctrinal of Princes , a translation of Isocrates' To Nicocles , and probably the earliest English book translated directly from Greek into English, consists of a collection of aphorisms, all advising moderation, addressed to monarchs. Pasquill the Playne , the first English pasquinade, is a comic dialogue on the ethical challenges involved in counseling a prince. Of That Knowledge Which Maketh a Wise Man is a direct imitation of a Platonic dialogue, in which Plato's confrontation with the Sicilian tyrant Dionysius is given dramatic form. A third dialogue, The Defense of Good Women , is the first printed English book that argues for the moral and political equality of women to men. Included in the volume are a general introduction to Elyot's life and political career, extensive critical introductions to each of the texts, full recordings of the variations between printed editions, and substantive notes.